EP961 Are there opportunities to improve the number of women able to start and tolerate treatment for ovarian cancer? European perspectives from the world ovarian cancer coalition's every woman study. (1st November 2019) - Reid, F; Oza, A; Bhatla, N; Blank, S; Cohen, R; Gardiner, D; Jones, A
Abstract : Introduction/Background: The aim of the World Ovarian Cancer Coalition Every Woman Study was to address the evidence gap relating to the experiences of women with ovarian cancer globally, with a view to improving survival and quality of life. Reports show 20% of UK women do not receive any treatment, and 15% of women die within 2 months of diagnosis. The chief concerns of European clinicians involved in the study were poor access to specialist surgeons, and delays in diagnosis contributing to poor performance status of women. Methodology: 1531 women from 44 countries participated in an online survey. Given global 5-year prevalence, results achieve a confidence level of 95% with a confidence interval of ± 2.5%. Some statistically significant country differences were seen compared to the average for all (p<0.01 and *p<0.05). 37 clinicians from 15 countries were consulted. Results: There were wide European variations in a number of metrics relating to the time period leading up to treatment including: women who did not know about ovarian cancer (Hungary 50.9%, Italy 56.3%*, Average 69.1%, Germany 79.3%); proportion of symptomatic women consulting a doctor (Germany 63.3%, Average 78.3%, UK 87.7%); proportion visiting a doctor within one month (Germany 77.3%, Spain 62.2%, Average 46.3%): diagnosis within one month of visiting doctor (UK 30%, Average 43.2%, Italy 62.3%); total estimated time to diagnosis (21.3 weeks in Germany to 31.5 weeks in Italy: proportion treated by gynaecologic oncologists in high volume centres where established networks and guidelines exist (e.g. Germany 50–60%, UK over 90%). Conclusion: The study shows wide variations between European countries in the experiences of women leading up to diagnosis and treatment, with no one country without barriers. This suggests there are opportunities to optimise the patient pathway in this critical time period, to ensure as many women as possible are able to start treatment. Disclosure: None of the authors have any conflicts of interest to disclose in relation to this Study. The study was funded by the World Ovarian Cancer Coalition (WOCC). WOCC received grants and pro bono support to enable translation of the women's survey from the following: Tesaro, Roche, Merck Pfizer Alliance.